Changes in household food security, access to health services and income in northern Lao PDR during the COVID-19 pandemic: a cross-sectional survey - Jennifer R Head; Phetsavanh Chanthavilay; Helen Catton; Ammaline Vongsitthi; Kelley Khamphouxay; Niphone Simphaly (BMJ Open)
Objectives We assessed the relative difficulty in meeting food needs during the COVID-19 pandemic compared with before; determined the relationship between pandemic-associated difficulties in food access and household, maternal and child food security; and identified resiliency-promoting strategies.Design A cross-sectional survey of households undertaken in November 2020.Setting Rural districts of Luang Prabang Province, Lao People’s Democratic Republic.Participants Households (N=1122) with children under 5 years.Primary and secondary outcomes measured Survey respondents reported the relative ease of access of food and healthcare as well as changes in income and expenditures compared with before March 2020. We determined indicators of food security and source of foods consumed for households, women and children, as well as prevalence of malnutrition in children under 5.Results Nearly four-fifths (78.5%) found it harder to meet household food needs during the pandemic. The most common reasons were increased food prices (51.2%), loss of income (45.3%) and decreased food availability (36.6%). Adjusting for demographics, households with increased difficulty meeting food needs had lower food consumption scores and child dietary diversity. Over 85% of households lost income during the pandemic. Decreased expenditures was associated with reliance on more extreme coping strategies to meet food needs. The households who experienced no change in meeting food needs produced a greater percentage of their food from homegrown methods (4.22% more, 95% CI 1.28 to 7.15), than households who found it more difficult.Conclusions Pandemic-associated shocks may have large effects on food insecurity. Action is needed to mitigate consequences of the pandemic on nutrition. Local food production and safety net programmes that offset income losses may help.